Соматизм «лицо» в функции субъекта русских и польских сравнительных конструкций - Chudyk, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article deals with the contrastive analysis of comparative constructions in which human face functions as a subject. Adjectives denoting some of their external features are the bases of comparison. The semantic and structural features of Russian and Polish comparison collocations of different types are analysed.
Keywords: сравнительная конструкция; основание сравнения; субъект сравнения; объект сравнения; соматизм «лицо»; comparative construction; basis of comparison; subject of comparison; object of comparison; somatism «лицо»